2016
DOI: 10.5152/eurasianjmed.2015.103
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Evaluation of Patients Seeking Rhinoplasty

Abstract: Objective: The aim of this study was to evaluate different determinants of the patient's psychosocial functioning that might possibly affect the outcome of rhinoplastic surgery. Materials and Methods:Forty-one patients undergoing rhinoplasty, consecutively admitted to and operated upon at the Department of Otolaryngology, Erzurum Regional Training and Research Hospital, Turkey, were studied with regard to their psychological characteristics. Results:In the patient group, Liebowitz anxiety, Liebowitz/ avoidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
5
1
2
Order By: Relevance
“…18 Similarly Kucur et al has observed that anxiety and depression scores among patients seeking rhinoplasty were higher than control group. 22 Results of this study also show that Anxiety was 48% while Depression was 30% in patients seeking rhinoplasty as compared to control group where anxiety was 25% and depression in 19% of patients, but contrary to these results Benjamin Jane in their study have shown higher prevalence of depression (50.6%) as compared to anxiety (32.9) among patients undergoing cosmetic surgery. 23 In the study by Ghahremani et al, it was observed that significant correlation was found among age, gender, marital status and job and that complaints of anxiety and depression was higher among female patients seeking rhinoplasty.…”
Section: Discussioncontrasting
confidence: 69%
“…18 Similarly Kucur et al has observed that anxiety and depression scores among patients seeking rhinoplasty were higher than control group. 22 Results of this study also show that Anxiety was 48% while Depression was 30% in patients seeking rhinoplasty as compared to control group where anxiety was 25% and depression in 19% of patients, but contrary to these results Benjamin Jane in their study have shown higher prevalence of depression (50.6%) as compared to anxiety (32.9) among patients undergoing cosmetic surgery. 23 In the study by Ghahremani et al, it was observed that significant correlation was found among age, gender, marital status and job and that complaints of anxiety and depression was higher among female patients seeking rhinoplasty.…”
Section: Discussioncontrasting
confidence: 69%
“…Surveys have shown significant negative effects of facial deformities on perceived employability, honesty, trustworthiness, and effectiveness, as well as the resulting impediment to interpersonal development [7]. Perception in society is a large factor of self-esteem, and unsightliness of the nose, whether in the individual or others' opinion, adversely affects self-image and self-value [8]. Effective rhinoplasty procedures are paramount to improving the quality of life for those with nasal dysfunctions and deformities.…”
Section: *Statement Of Significancementioning
confidence: 99%
“…Kozmetik cerrahi yaptıranların görünüşünü, tatminkarlığını ve özgüvenini arttırdıkça, çok sayıda psikolojik ve sosyal faktörler de değerlendirmeye alınmaya başlandı 6,9 .…”
Section: Discussionunclassified
“…Green ve arkadaşları vücut imajı ile ilgili tatminsizlik ve anksiyete ile mental rahatsızlıkların hastaları estetik cerrahiye zorladığını belirtmişlerdir 8 . Bazı bilim adamları estetik cerrahi yaptıran çoğu kişinin özbeğenisinin fiziksel görüntü bağıntılı olduğunu ve bu yüzden cerrahi değişim aradıklarını ifade etmişlerdir 9 . Diğer araştırmacılar ise bu kişilerin psikolojik olarak tamamen sağlıklı olduklarını ve sadece görüntülerinin daha iyi olmasını amaçladıklarını belirtmişlerdir [10][11][12] .…”
Section: Introductionunclassified